The Influence of Work Discipline and Organizational Culture on Employee Performance with Work Motivation as an Intervening Variable: The Case Study of Dinas Perumahan dan Kawasan Pemukiman OKU Regency in Baturaja - Loga, Mutia Inka; Rahayu, Sri; Tobari, Tobari (International Journal of Marketing & Human Resource Research, 2024)
This research aims to determine the influence of work discipline and organizational culture on employee performance, with work motivation as an intervening variable at the OKU Housing and Settlement Area Service in Baturaja. This type of research is associative. The variables researchers use are work discipline, organizational culture, work motivation, and performance. The sample in this research was 125 employees of the OKU Regency Housing and Settlement Area Service in Baturaja who were selected using cluster sampling. The data used in this research is primary data collected through a questionnaire. The data analysis technique used is Structural Modeling Equation (SEM) with the Lisrel Program Application. The results of this research show that (1) work discipline has a positive and significant effect on employee performance, (2) organizational culture has a positive and significant effect on employee performance, (3) work discipline has a positive and significant effect on employee work motivation, (4) organizational culture has an insignificant effect on employee work motivation, (5) work motivation has a positive and significant effect on employee performance at the OKU Regency Housing and Settlement Area Service in Baturaja